Studies on the reactivity pattern of in situ generated tetraethylammonium superoxide with 2-oxazolin-5-ones - Singh K.N.; Kumar R. (My University, 2025)
A variety of 2-oxazolin-5-ones have been allowed to react under the mild reaction conditions of potassium superoxide and tetraethylammonium bromide in dry dimethylformamide at room temperature. Different products are obtained depending on the substituents attached to the C-4 position.